The fundamental need for unifying phenotypes in sudden unexpected pediatric deaths - Wojcik, Monica H.; Poduri, Annapurna H.; Holm, Ingrid A.; MacRae, Calum A.; Goldstein, Richard D. (Frontiers in Medicine, 2023)
A definitive, authoritative approach to evaluate the causes of unexpected, and ultimately unexplained, pediatric deaths remains elusive, relegating final conclusions to diagnoses of exclusion in the vast majority of cases. Research into unexplained pediatric deaths has focused primarily on sudden infant deaths (under 1 year of age) and led to the identification of several potential, albeit incompletely understood, contributory factors: nonspecific pathology findings, associations with sleep position and environment that may not be uniformly relevant, and the elucidation of a role for serotonin that is practically difficult to estimate in any individual case. Any assessment of progress in this field must also acknowledge the failure of current approaches to substantially decrease mortality rates in decades. Furthermore, potential commonalities with pediatric deaths across a broader age spectrum have not been widely considered. Recent epilepsy-related observations and genetic findings, identified post-mortem in both infants and children who died suddenly and unexpectedly, suggest a role for more intense and specific phenotyping efforts as well as an expanded role for genetic and genomic evaluation. We therefore present a new approach to reframe the phenotype in sudden unexplained deaths in the pediatric age range, collapsing many distinctions based on arbitrary factors (such as age) that have previously guided research in this area, and discuss its implications for the future of postmortem investigation.